(untitled) ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2023)
Background: Studies pertaining farm tourism chiefly highlights positivistic methodologies and quantitative approaches. However, there is need to explore, describe and better understand the intricacies of tourism impacting the farm, the families and rural surroundings. Interpretative research methods are comprehensive and ease off compound understanding of human dynamics involved in farm tourism. This phenomenological study explores the farm tourism experiences in Shimla from the perspective of both hosts and guests. Objective:The aim of the study was to understand different motivations people have to run a farm tourism business, and what motivates visitors to seek holidays at these destinations. Methodology: The personal narratives of hosts interviewed clarified assumptions about the motives for embracing farm tourism, the most significant being meeting new people. Results: Findings suggest that tourists were motivated with the desire to unwind in the serene rural landscape and to learn about rural lifestyle infused with culture and Horti practices. Incidentally, the stimulus for both the classes were found to be highly coherent with each other indicating bright future of farm stay tourism in the region. Conclusion: Both guest and host motivations were found to be compatible indicating a prospective future for farm tourism.